Analisis Peran Akuntansi Manajemen Dalam Pengendalian Biaya - Ai Nur Rohimah; Purwanti (GLOBAL SCIENTS PUBLISHER, 2025)
This research aims to analyze the role of management accounting in cost control in companies. Management accounting has a strategic role in identifying, measuring and controlling costs that arise in production and operational processes. Using qualitative descriptive methods, this research examines various management accounting techniques, such as cost budgeting, variance analysis, and the cost-volume-profit (CVP) method, in the context of cost control. The research results show that implementing effective management accounting can help companies optimize resource use, reduce waste and increase operational efficiency. Apart from that, management accounting also plays an important role in making strategic decisions related to pricing, investment and financial planning. This research provides recommendations for companies to maximize the function of management accounting as a cost control tool to achieve better financial and operational goals.